Beyond the Euro: limits to economic policy in the EU - Boixadera Bosch , Ramón; Portella Carbó , Ferrán (Revista de Economía Crítica, 2024)
The euro’s crisis is often theorized as that of a fixed exchange-rate monetary system, whose rigidity in the face of heterogenous national economies is the main factor behind the Eurozone's troubles. We argue instead that the euro should be primarily considered as a successful attempt to further the integration of the European economy within an ordoliberal framework, part of an institutional continuum stretching from the European Single Market to the present. Further, we note that the constraints placed by the euro on national economies are deeply entangled with those deriving from EU membership, so that both are likely to weigh on any attempt to break with neoliberalism at national level.